2007
DOI: 10.1111/j.1365-2095.2007.00494.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two soybean meals fed to yellow perch (Perca flavescens)

Abstract: Aquaculture of yellow perch (Perca flavescens) has been increasing, yet there have been few nutritional studies and no evaluations of alternative protein sources in diets. Solventextracted, dehulled soybean meal (SBM) and expelledextruded soybean meal (exSBM) were fed to yellow perch to evaluate their effectiveness in replacing dietary fish meal (FM) in isonitrogenous practical feed formulations. Both soy ingredients were incorporated in graded amounts from 100 to 730 g kg )1 of the diet. Feed consumption, wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 31 publications
3
36
0
1
Order By: Relevance
“…This may explain performance loss of turbots fed PP-based diets in this study. Previous studies already revealed negative effects of diets containing soy bean meal (SBM) or soy protein concentrate (SPC) on feed consumption and growth performance in turbot (Bonaldo et al, 2011;Day and Plascencia GonzĂĄlez, 2000) and other fish species Kasper et al, 2007;Kaushik et al, 1995;Kissil et al, 2000). However, during the process of SPC production most antinutritional factors should be destroyed, only phytate may be concentrated with the protein fraction (Gatlin et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This may explain performance loss of turbots fed PP-based diets in this study. Previous studies already revealed negative effects of diets containing soy bean meal (SBM) or soy protein concentrate (SPC) on feed consumption and growth performance in turbot (Bonaldo et al, 2011;Day and Plascencia GonzĂĄlez, 2000) and other fish species Kasper et al, 2007;Kaushik et al, 1995;Kissil et al, 2000). However, during the process of SPC production most antinutritional factors should be destroyed, only phytate may be concentrated with the protein fraction (Gatlin et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Content of dietary fish meal can be reduced from 26 to 32% for cuneate drum (Wang et al ); tiger puffer, Takifugu rubripes (Lim et al ); and sharpsnout seabream, Diplodus puntazzo (Hernandez et al ); when fish meal is replaced with SBM. Content of dietary fish meal is 20% for yellow perch, Perca flavescens (Kasper et al ), and gilthead sea bream (Martinez‐Llorens et al ), and 5% for red drum (McGoogan and Gatlin ) when SBM is used as a fish meal substitute. Generally, dietary protein and fish meal levels are higher in carnivorous fish species than in herbivorous or omnivorous fish species.…”
Section: Discussionmentioning
confidence: 99%
“…Lower growth performance and/or apparent digestibility coefficients for dry matter, energy, lipid, and/or protein in SBM-containing diets for other carnivorous species such as European sea bass, Dicentrarchus labrax (Tibaldi et al, 2006), largemouth bass, Micropterus salmoides (Portz and Cyrino, 2004), gilthead sea bream, Sparus aurata (Robaina et al, 1995;Venou et al, 2006), yellow perch, Perca Flavescens (Kasper et al, 2007), fingerling red drum, Sciaenops ocellatus (Reigh and Ellis, 1992), Australian snapper (red sea bream; squirefish), Pagrus (Chrysophyrs) auratus (Quartararo et al, 1998) Paralichthys olivaceus (Deng et al, 2006) have also been observed. Lower weight gain, feed efficiency, and protein efficiency ratio at higher inclusion levels of SBM have been reported in juvenile cobia, Rachycentron canadum (Chou et al, 2004;Zhou et al, 2005), although specific effects on digestive function are not known.…”
Section: Legumesmentioning
confidence: 99%